FAKTOR - FAKTOR YANG MEMPENGARUHI KEBERHASILAN MANAJEMEN PENGETAHUAN DALAM INSTITUSI PERGURUAN TINGGI - Calandra Alencia Haryani; Suryasari Suryasari (Universitas Multimedia Nusantara, 2020)
Knowledge Management (KM) has become an integral factor for many organizations to achieve their goals. Currently, Higher Education Institutions (HEI), have also joined the practices of KM, to enhance the institution’s quality, boosting the effectiveness, developing human resource, and constructing the knowledge culture within the institution. The aim of this study is to observe the constructed Critical Success Factor (CSF) model affecting the implementation of KM. This study follows Kitchenham’s Systematic Literature Review (SLR) procedures from 15 eligible journal articles obtained through KM related literature. The results, analysis, and discussions are elaborated in the paper.